PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO BERBANTUAN APLIKASI WONDERSHARE FILMORA PADA MATERI KEKAYAAN BUDAYA INDONESIA KELAS IV SDN ARAMIYAH - Cut Utia Rahmi Z; Sukirno; Mahlianurrahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine the validity, practicality, and effectiveness of video-based learning media assisted by the Wondershare Filmora application. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation.The validation results showed that t he material expert gave a percentage of 93% with a “very valid” criterion, the media expert gave 83% with a “very valid” criterion, the language expert gave 97% with a “very valid” criterion, and the learning interest questionnaire validation obtained 97.5% with a “very valid” criterion. The practicality results from the teacher response questionnaire obtained a percentage of 95.7% with a “very practical” criterion, while student responses obtained 92.4% with a “very practical” criterion. The normality test of students’ learning interest before and after the intervention showed a pretest significance value of 0.562 ≥ 0.05 and a posttest significance value of 0.812 ≥ 0.05. Therefore, it can be concluded that the data used in this study were normally distributed. Furthermore, the Paired Sample T-test showed that the calculated t-value (t_calculated) was 27.261, while the t-table value (t_table) was 2.086. Thus, H₁ was accepted and H₀ was rejected, indicating that there was an increase in students’ learning interest after using video-based learning media. Based on the N-Gain Score calculation, the average posttest score was 77.7956, which falls into the effective category of students’ learning interest. This indicates that the use of video-based learning media assisted by the Wondershare Filmora application is effective in increasing the learning interest of fourth-grade students. In conclusion, the video-based learning media assisted by the Wondershare Filmora application are valid, effective, and practical for fourth-grade students at SDN Aramiyah.